Living and Working in Tall Buildings: Satisfaction and Perceived Benefits and Concerns of Occupants - Ng, Cheuk Fan (Frontiers in Built Environment, 2017)
In the last few decades, tall buildings of 30 to over 100 stories are becoming more common in modern cities around the world, especially in Asia and the Middle-East, according to the Council on Tall Buildings and Urban Habitat. Extensive research has focused on the technical aspects of erecting tall buildings, yet few recent studies have been conducted to examine occupants’ experiences and responses. To assess what is already known about living and working in these tall buildings and to provide future directions for research, this paper reviews recent empirical studies on occupants’ perception of tall buildings, and physiological and psychological experiences in relation to its tallness. Occupants perceive better view, less noise, and better air quality as benefits for living and working on higher floors than on lower floors. However, occupants also expressed concerns about height, difficulty with vertical transportation, strong wind, and escape in case of fire. Note that the methodologies used in many of the self-reported studies are relatively weak. Given the scarcity of research regarding human responses, this mini-review aims to encourage behavioral scientists to collaborate with building science researchers to advance our understanding of human-environmental relations in this new habitat.